The institutionalisation of biology in the British Association for the Advancement of Science, 1866-1894 - Juan Manuel Rodriguez-Caso (História, Ciências, Saúde: Manguinhos, 2022)
Abstract Biology, like most scientific disciplines, emerged in the nineteenth century. However, disciplinary institutionalisation processes are not linear; a concept can be proposed, but not develop. Biology originated in the presence of established traditions such as anatomy, physiology, botany, and zoology, which represent the thematic and practical diversity under which it was understood. Based on the records of the annual meetings of the British Association for the Advancement of Science, the process by which biology emerged will be described. We will also recount how the discipline underwent changes throughout the century, where contrasting methodologies and theories were emphasized at different times.